Incidence of out-of-hospital cardiac arrests and survival rates after 1 month among the Japanese working population: a cohort study - Yoshihisa Fujino; Haruhiko Abe; Yasunobu Yamagishi; Yasushi Oginosawa; Keishiro Yagyu; Taro Miyamoto; Keita Tsukahara; Hisaharu Ohe; Ritsuko Kohno (BMJ Open)
Objectives The prevention and improvement of the prognosis of out-of-hospital cardiac arrests (OHCAs) are important issues especially with respect to their social and economic significance in working populations. The age distribution of the working population in Japan is expected to change continually due to its ageing society and extension of retirement; however, few reports have examined the long-term condition of OHCA in the working population, defined by age. The aim of this study was to determine the incidence of OHCAs and the survival rates after 1 month, among the Japanese working population, defined by age, considering the changing age distribution.Design and setting We analysed the All-Japan Utstein registry, a prospective, nationwide, population-based, observational registry (2005–2016).Participants From the registry, 212 961 patients with OHCA from the Japanese working population (defined aged 20–69 years), with only cardiogenic aetiology participated in this study. These patients were further divided into four groups according to the type of citizen bystander (family, friends, work-colleagues and passers-by).Primary and secondary outcome measures The main outcomes were 1-month survival with favourable neurological outcomes.Results The incidence of OHCAs, in any age group, was almost constant during the 12-year period. The work-colleagues had the best prognosis despite having significantly longer times to initial defibrillations compared with the passers-by (13 vs 12 min, respectively, p<0.001) that was associated independently with 1-month survival with favourable neurological outcomes (adjusted OR: 0.94 (1 min increments), p<0.001).Conclusions In the 12-year period, the incidence of OHCAs in any age group remained almost constant, whereas the prognosis improved each year. Reducing the time to initial defibrillation may further improve the prognosis of OHCAs with a work-colleague bystander.